Editorial Board (European Journal of Transport and Infrastructure Research, 2017)
Prof.dr.ir. C.G. (Caspar) Chorus c.g.chorus@tudelft.nl Editor-In-Chief Delft University of Technology, The Netherlands Dr. O. (Oded) Cats o.cats@tudelft.nl Associate Editor Delft University of Technology, The Netherlands Prof.dr. B. van Wee g.p.vanwee@tudelft.nl Delft University of Technology, The Netherlands Prof.dr.ir. V.A.W.J. Marchau v.marchau@fm.ru.nl Radboud University Nijmegen, The Netherlands Prof.dr.ir. S. Hoogendoorn s.p.hoogendoorn@tudelft.nl Delft University of Technology, The Netherlands Dr. D. Stead d.stead@tudelft.nl Delft University of Technology, The Netherlands Prof.dr.ir. L. Tavasszy l.a.tavassszy@tudelft.nl Delft University of Technology, The Netherlands Prof.dr.ir. R.E.C.M. Van der Heijden r.vanderheijden@fm.ru.nl Radboud University Nijmegen, The Netherlands Prof.dr. E. Van de Voorde eddy.vandevoorde@uantwerpen.be University of Antwerp, Belgium Prof.dr. F. Witlox frank.witlox@ugent.be Ghent University, Belgium Advisory Board Peter Nijkamp (Chairman) VU University, The Netherlands Kay Axhausen ETH Zurich, Switzerland David Banister University College London, UK Michel Beuthe Facultés Universitaires Catholiques de Mons, Belgium Michel Bierlaire EPFL Lausanne, Switzerland Piet Bovy Delft University of Technology, The Netherlands Oliver Carsten Leeds, University, UK David Hensher University of Sydney, Australia Veli Himanen Technical Research Centre of Finland (FIN), Finland Martin Lanzendorf Goethe Universität Frankfurt, Germany Rico Maggi University of Zürich, Switzerland Patricia Mokhtarian UC Davis, USA Tae Oum University of British Columbia, Canada Robert E. Paaswell City University of New York, USA Aura Regiani University of Bologna, Italy Piet Rietveld (†) VU University, The Netherlands Daniel Shefer Technion-Israel Institure of Technology, Israel Jos van Ommeren VU University, The Netherlands Erik Verhoef VU University, The Netherlands Joan Walker UC Berkeley, USA